2019
DOI: 10.3917/spub.190.0219
|View full text |Cite
|
Sign up to set email alerts
|

De quelles preuves scientifiques disposons-nous concernant les effets des forêts et des arbres sur la santé et le bien-être humains ?

Abstract: Dans la société actuelle, les maladies liées au mode de vie jouent un rôle de plus en plus important dans les causes de mauvaise santé. L’accès et le séjour dans des environnements qui contiennent des éléments naturels tels que les forêts, les parcs et les jardins ont attiré l’attention pour leur capacité à favoriser la santé et le bien-être humains. Un domaine de recherche à part entière s’est développé pour expliquer et attester du lien entre accès et activités dans la nature et santé humaine. L’action COST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 104 publications
0
16
0
Order By: Relevance
“…Restorative environments are defined, according to von Lindern et al (2016), as environments that both permit and promote restoration. Several studies have shown that spending time in natural environments is positive for human health (e.g., Egorov et al, 2016;Nilsson et al, 2019). People who suffer from high levels of stress restore their capacities when staying in and/or being exposed to natural environments but not so in built-up environments (Ulrich, 1993;van den Bosch and Bird, 2018).…”
Section: On Innate Preferences Originated Through Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Restorative environments are defined, according to von Lindern et al (2016), as environments that both permit and promote restoration. Several studies have shown that spending time in natural environments is positive for human health (e.g., Egorov et al, 2016;Nilsson et al, 2019). People who suffer from high levels of stress restore their capacities when staying in and/or being exposed to natural environments but not so in built-up environments (Ulrich, 1993;van den Bosch and Bird, 2018).…”
Section: On Innate Preferences Originated Through Evolutionmentioning
confidence: 99%
“…In the right branch of the cluster tree (Figure 1), there are several environments that can be described as restorative: open landscapes with deciduous forests, hills, and streams in cluster six; appealing and tranquil sounds and scents in cluster seven; groves, meadows, and pastures in cluster eight; friendly animals in cluster nine as well as fruit trees, flowers, and birdsong in cluster ten. It is well known that staying in and/or being exposed to natural environments is linked to restorative stressreducing effects, such as lowered cortisol levels and blood pressure, and these natural areas are described as having the qualities found in the right part of the cluster tree (Twohig-Bennett and Jones, 2018; van den Bosch and Bird, 2018; Nilsson et al, 2019). Several frequently quoted researchers claim that people through evolution have received higher preferences for particular objects and phenomena in certain natural landscapes.…”
Section: Environments People Actively Seek For Restorative Environments: Biophiliamentioning
confidence: 99%
See 1 more Smart Citation
“…Social and psychological benefits associated with trees and nature are also well recognized. Stronger sense of community and connection with other people, as well as increasing feeling of safety and enjoyment of everyday life is reported [26,[37][38][39][40][41][42][43].…”
Section: Perception Of Tree Benefits and Threatsmentioning
confidence: 99%
“…People who need time of "healthy" loneliness, in the bosom of nature can calm down, relax, find an internal balance, nature gives solace, a feeling of freedom and privacy, outdoor activity positively influences physical health, helps fight obesity, respiratory diseases, sight and the backbone. Man strives for a connection with nature through the desire for health, well-being, and greater efficiency [42,[54][55][56]. The innate desire to come in contact with nature is called biophilia, a genetically coded basic need for life [57].…”
Section: Perception Of Tree Benefits and Threatsmentioning
confidence: 99%